A review of the global ecology, genomics, and biogeography of the toxic cyanobacterium, Microcystis spp - Harke, Matthew J.; Steffen, Morgan M.; Gobler, Christopher J.; Otten, Timothy G.; Wilhelm, Steven W.; Wood, Susanna A.; Paerl, Hans W. (Harmful algae, 2016)
This review summarizes the present state of knowledge regarding the toxic, bloom-forming cyanobacterium, Microcystis, with a specific focus on its geographic distribution, toxins, genomics, phylogeny, and ecology. A global analysis found documentation suggesting geographic expansion of Microcystis, with recorded blooms in at least 108 countries, 79 of which have also reported the hepatatoxin microcystin. The production of microcystins (originally “Fast-Death Factor”) by Microcystis and factors that control synthesis of this toxin are reviewed, as well as the putative ecophysiological roles of this metabolite. Molecular biological analyses have provided significant insight into the ecology and physiology of Microcystis, as well as revealed the highly dynamic, and potentially unstable, nature of its genome. A genetic sequence analysis of 27 Microcystis species, including 15 complete/draft genomes are presented. Using the strictest biological definition of what constitutes a bacterial species, these analyses indicate that all Microcystis species warrant placement into the same species complex since the average nucleotide identity values were above 95%, 16S rRNA nucleotide identity scores exceeded 99%, and DNA–DNA hybridization was consistently greater than 70%. The review further provides evidence from around the globe for the key role that both nitrogen and phosphorus play in controlling Microcystis bloom dynamics, and the effect of elevated temperature on bloom intensification. Finally, highlighted is the ability of Microcystis assemblages to minimize their mortality losses by resisting grazing by zooplankton and bivalves, as well as viral lysis, and discuss factors facilitating assemblage resilience.